Dynamic Changes of Molecular Subtype Classification and Genomic Classifier Scores in High-Risk Prostate Cancer Patients Undergoing Pre-Operative Stereotactic Body Radiation Therapy - Diven, M.; Hakansson, A.; Liu, Y.; Davicioni, E.; Dillard, A.; Khani, F.; Wolfe, S.; Hu, J.C.; Scherr, D.S.; McClure, T.D.; Barbieri, C.E.; Nagar, H.; et al. (International journal of radiation oncology, biology, physics, 2023)
The radiobiology of irradiated human prostate cancer (PCa) remains poorly understood as irradiated tissues often remain in situ. PREPARE-SBRT (NCT03663218) is a clinical trial testing the safety of neoadjuvant MRI-guided stereotactic body radiation therapy (SBRT) for men with high-risk PCa. We leveraged paired samples from pre-treatment biopsy and irradiated prostatectomy (RP) specimens to evaluate transcriptomic changes in irradiated tumors at acute timepoints following SBRT. Tumor RNA expression profiles were generated using Decipher GRID by Veracyte on 12 subjects enrolled on NCT03663218 with paired pre/post-SBRT tissues (n = 24). Descriptive statistics using Decipher Genomic Classifier (GC) Score [0-1] and GC risk group (low/int/high) were generated from a validated 22-gene GC. Tumor biology signatures reported as dichotomous variables evaluated changes in androgen receptor (AR) activity [higher v lower] and cell cycle progression (CCP) [lower v higher]. Decipher prostate subtype classifier [PSC, luminal differentiated (LD), luminal proliferating (LP), basal immune (BI), basal neuroendocrine like (BN)] classification and PAM50 molecular subtype [luminal A (lumA), luminal B (lumB), basal] at pre/post-SBRT timepoints were reported. A control cohort of transcriptomic profiles of 803 matched untreated biopsy and RP samples from the same patients were used to control for signature differences attributable to sample type. The median pre- and post-SBRT GC scores were 0.55 and 0.72 (Δ+0.17), respectively. By comparison, median GC scores in a control cohort (n = 803) of biopsy and RP specimens were 0.50 and 0.56 (Δ+0.06), respectively. SBRT increased GC score in 9/12 subjects (75%) with a median increase of 0.3. Changes in GC score resulted in reclassification of baseline GC risk in 7 of 12 subjects with 71% of reclassified subjects (5/7) transitioning to a higher genomic risk. 92% of subjects (11/12) had higher AR activity scores at baseline. Of this subgroup, 5/11 (45%) converted to lower AR activity score after SBRT. CCP signatures remained stable in 9 of 12 subjects (75%) with 7/12 subjects exhibiting lower CCP score at baseline and only 1 subject transitioning from lower to higher CCP score. Distribution of PAM50 molecular subtype at baseline and after SBRT was lumA (33>53%), lumB (25>17%), basal (42>25%) resulting in 83% of subjects (10/12) annotated to a different PAM50 molecular subtype at pre/post-SBRT assessment. PSC subtype distribution at baseline was LD (33%), LP (25%), BI (33%) and BN (8%). Strikingly, after SBRT, 92% (11/12) of subjects were classified as BI molecular subtype with several immune activation signatures also increased after SBRT. A majority of subjects demonstrate a post-SBRT increase in GC score with reclassification of genomic-prognostic risk group in 58%. An enrichment of the basal-immune molecular subtype was observed following SBRT suggesting a convergence towards this biology in irradiated tumors.